MENGUNGKAP KOSAKATA DALAM PROSESI ADAT PERKAWINAN ETNIS KAILI DI KOTA PALU - Nurmiah NFN; Aminah NFN (Balai Bahasa Sulawesi Tengah, 2020)
AbstractThis paper had aimed to describe to vocabularies using in traditional ritual of marriage of Kaili’s ethnic in Palu city. Method applies was descriptive one. The data sources was the oral speechs which was using in the ritual. The data collecting was taken by observation technique and extended by non participate observation technique and recorded technique. The result were described that there were three stages in traditional ritual of marriage in Palu, : (1) before marriage, (2) in-process marriage, and(3) after marriage. There were nineteen vocabularies which related with the ritual; eight in stage of before marriage, eight in-process, and three vocabularies in the stage of after marriage. Those nineteen vocabularies were verbs, nouns, verb phrases, noun phrases, and proverb.Keywords: Kaili’s ethnic, vocabularies, marriage